Scalar capital as ingredient of success in conservation governance: evidence from Melanesia - Cheok, Jessica; Weeks, Rebecca; Morrison, Tiffany H.; Pressey, Robert L. (Global environmental change, 2020)
•Scalar capital shapes effective conservation governance.•Yet, scalar capital is typically overlooked when evaluating conservation governance.•Flows of scalar capital in conservation governance are not unidirectional.•Effective conservation governance requires iterative cycling between multiple scales.•Scalar capital needs explicit consideration next to other capital types in conservation. Problems of scale abound in the governance of complex social-ecological systems. Conservation governance, for example, typically occurs at a single scale, but needs to inform governance and action at other scales to be truly effective at achieving social and ecological outcomes. This process is conventionally conceived as unidirectional – either scaling down or scaling up – in the way it both exploits and creates the natural, social, human, institutional, and financial resources and benefits that are collectively known as conservation ‘capital’. Here we analyse multiscale conservation governance and the different types of capital that impede or facilitate its effectiveness. Comparative analysis of conservation planning in Papua New Guinea and the Solomon Islands, through in-depth document review, key informant interview, and participant observation, reveals limited evidence of unidirectional processes. Instead, we observe multidirectional scaling pathways, cultivated by the following six scale-explicit characteristics of effective conservation governance: 1) multiscale understanding, 2) scale jumping, 3) scaled leadership characteristics, 4) scaled stakeholder engagement, 5) scaled policy frameworks, and 6) scaled institutional settings. While the latter four are familiar concepts, though not always recognised as explicitly scalar, we know little about the first two attributes of conservation governance. Based on this novelty and relevance, we propose a new form of capital – ‘scalar capital’ – to complement natural, social, human, institutional, and financial capitals as both input and outcome of effective conservation governance. We find that scalar capital facilitates flows of different resources (data, conservation objectives, practitioner experience, institutional support, and funding) in multiple directions. Critically, we present empirical evidence that conservation governance can foster scalar capital to improve outcomes across multiple scales.